Understanding cancer trends - Thun, Michael (Henry Stewart Talks, 2009)
Current trends in cancer incidence, mortality and relative survival in the US, Understanding how improvements in prevention, early detection and treatment affect these trends, How demographic changes affect the number of cancer cases and deaths but not the age-standardized incidence or death rates, Specific cancer sites for which the incidence and/or death rates are changing, Role of prevention, early detection, and improvements in treatment in reducing the burden of cancer
Archived at 2021/02/25